2015
DOI: 10.1002/2327-6924.12191
|View full text |Cite
|
Sign up to set email alerts
|

Access to care based on state nurse practitioner practice regulation: Secondary data analysis results in the Medicare population

Abstract: Purpose To examine access to care in the Medicare population based on state nurse practitioner (NP) practice regulation. Data sources Secondary data analysis of the Medicare Current Beneficiary Survey Access to Care 2011 dataset. Items used to measure access to care were usual source of care, appointment waiting times, and difficulties encountered. States were designated as full, reduced, or restricted NP practice based on data from the American Association of Nurse Practitioners State Regulatory Map. Conclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…To date, several studies investigated the impact of various regulatory barriers on NP role in care delivery and patients’ access to care (Barnes et al, 2016, Cross and Kelly, 2015, Graves et al, 2016). In contrast, comparatively little research has focused on the organizational structures in health care settings employing NPs and how organizations utilize NPs in care delivery as primary care providers with their own patient panel within the same federal and state regulatory environment.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several studies investigated the impact of various regulatory barriers on NP role in care delivery and patients’ access to care (Barnes et al, 2016, Cross and Kelly, 2015, Graves et al, 2016). In contrast, comparatively little research has focused on the organizational structures in health care settings employing NPs and how organizations utilize NPs in care delivery as primary care providers with their own patient panel within the same federal and state regulatory environment.…”
Section: Introductionmentioning
confidence: 99%
“…Richards and Polsky (2016) found improved access to care for Medicaid beneficiaries in practices that both employed more providers, including NPs and physician assistants (PAs), and were located in states with the least restrictive SOP. In one study, a sample of Medicare beneficiaries reported shorter wait times for appointments and less difficulty accessing care in states with more restrictive NP SOP regulations (Cross & Kelly, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Despite this, there is a growing shortage of primary care physicians that is expected to worsen due to an aging population, the rising prevalence of chronic diseases, and the expansion of coverage under the Affordable Care Act (U.S. Department of Health and Human Services [USDHHS], ). One proposed solution is to better integrate nurse practitioners (NPs) and physician assistants (PAs) into the primary care workforce (Cassidy, ; Cross & Kelly, ; USDHHS, ; Van Vleet & Paradise, ), but the appropriate role of NPs in primary care remains the subject of debate. While the majority of NPs favor greater scope of practice for their profession, they face resistance from some physicians (American Academy of Family Physicians [AAFP], ; Donelan, DesRoches, Dittus, & Buerhaus, ).…”
Section: Introductionmentioning
confidence: 99%